Polarization holography using diarylethene dye (b1536) doped polymer - Tan, Wei Jie. (2010)
Polarization holography has great potential to achieve 100% diffraction efficiency, even for thin holograms, and removal of twin image for 3D display. In order to utilize this form of holography, a media capable of recording light polarization is required. In this project, thin films of diarylethene dye (cis-1,2-dicyano-1,2-bis(2,4,5-trimethyl -3-thienyl) ethane, also called B1536) doped PMMA (Poly (methyl methacrylate)), PC (Polycarbonate) and PVA (Poly Vinyl Alcohol) films were developed in order to test the dye’s suitability for polarization holography application. The holographic performances of these media were characterized for light of wavelength 532nm with different polarization configuration, e.g. parallel linearly, orthogonal linearly and orthogonal circularly polarized light. The effects of the different writing and reading beams were compared and contrasted. A maximum diffraction efficiency of 25.4% was achieved using orthogonal circularly polarized writing and reading beams on a 5%wt polycarbonate film doped with B1536. Polycarbonate was found to be the most suitable matrix for the B1536 doped media for polarization holographic recording at the green light range.